TINDAK TUTUR EKSPRESIF DALAM TALK SHOW INDONESIA LAWAK KLUB - Septiani, Zelli; Juita, Novia; Emidar, Emidar (Universitas Negeri Padang, 2016)
ABSTRACTÂ The purpose of this study was to describe: (1) The form of expressive speech acts, (2) Strategy speak used in Talk Show Indonesia Comedy Clubs. The research is a qualitative research with descriptive methods. The methods used in data collection is a method refer to. The data collection technique is a technique involved refer free conversation (SBLC), record, and record. Sources of data in this study is a Talk Show Indonesia Comedy Clubs (ILK) in Trans7. Expressive utterances of speakers in Talk Show Indonesia Comedy Clubs.Teknik used as the data used to analyze the data as follows: (1) Identify, (2) Classification, (3) Interpreting, (4) discussion, and (5) Draw conclusions. Based on the findings, we can conclude the following. (1) There are six forms of expressive speech acts used in Talk Show Indonesia Comedy Clubs, namely expressive speech acts to thank, congratulate, apologize, praise, criticize, and invited. Expressive speech acts the most predominant use is expressive speech acts criticized and least used is expressive speech acts apologize. (2) There are four strategies bertutur used in Talk Show Indonesia Comedy Clubs, which speak frankly without further ado in the context of the speaker more powerful solidarity is already familiar, speak frankly with the preamble of politeness positive in the context of the speaker more powerful solidarity not yet familiar , speak frankly with the preamble of negative politeness in the context of solidarity is more powerful speaker yet familiar, and spoken vaguely in the context of a more powerful speaker yet familiar solidarity. Speak widely used strategy is the strategy speak frankly without further ado in the context of a more powerful speakers of solidarity is already familiar.Â Kata kunci: tindak tutur ekspresif, Indonesia Lawak Klub